Acute Colonic Pseudo-obstruction: Defining the Epidemiology, Treatment, and Adverse Outcomes of Ogilvie's Syndrome. Issue 2 (February 2016) - Ross, Samuel W.; Oommen, Bindhu; Wormer, Blair A.; Walters, Amanda L.; Augenstein, Vedra A.; Heniford, B. Todd; Sing, Ronald F.; Christmas, A. Britton
Acute colonic pseudo-obstruction (ACPO) is a rare but often fatal disease. Herein, we present the largest study to date on ACPO. The National Inpatient Sample was queried for ACPO diagnoses from 1998 to 2011. Patients were analyzed by treatment into four groups: medical management (MM), colonoscopy alone [(endoscopy-only group) ENDO], surgery alone (SURG), or surgery and colonoscopy (SAC). Logistic regression was used to identify predictors of adverse outcomes by treatment group. There were 106, 784 cases of ACPO: 96, 657 (90.5%) MM, 2, 915 (2.7%) ENDO, 6, 731 (6.3%) SURG, and 481 (0.5%) SAC. The medical complication (45.7%), procedural complication (15.9%), and mortality rates (7.7%) were high. Increasing procedure invasiveness was independently associated with higher odds of medical complications, procedural complications, and death ( P < 0.0125). The odds of death were significantly higher in the ENDO [odds ratio (OR) = 1.2], SURG (OR 1.4), and SAC (OR = 1.8) groups ( P < 0.0125). Those who fail MM and require procedures have increasing morbidity and mortality with increasing invasiveness, likely reflecting the severity of their conditions.